Gender Diversity, Board Composition, Intellectual Capital and Its Effect on Firm Performance - Lestari, Rehgita Ayu (Universitas Negeri Semarang, 2021)
The purpose of this study was to analyze the influence of gender diversity, board of directors, board of commissioner, independent commissioner, and intellectual capital on firm performance. The population in this study is all consumer goods industry sector companies listed on the Indonesia Stock exchange for the period 2014-2018. Sampling in this study using purposive sampling, as many as 40 companies were selected as samples with a total 200 observation. The analysis method used in this research is regression analysis with fixed effect model approach and hypothesis testing. The result showed that the board of directors, the proportion of independent commissioner, and intellectual capital have positve and significant effect on firm performance. Menwhile, gender diversity and the board of commissioner have no effect on firm performance. The advice provide is for investors and companies to pay attention and conside the variables that effect on firm performance such as the board of directors, the proportion of independent commissioners and intellectual capital as a consideration to assess the firm performance. As forfurther research, the gender diversity variable can be measured using other proxies such as the blau index or so on. Firthermore, researcher are also expected to add other independent variables that affect on firm performance such as political connection, firm size, and manajerial ownership